Seasonal Distributions of Methane in a Populous Urban Coastal Sea Area - Tseng, Hsiao-Chun; Lin, Chia-Chia; Pan, Hui-Juan; Han, Yokie Tai Yuh; Gong, Gwo-Ching (Frontiers in Marine Science, 2022)
Methane (CH4) is an important greenhouse gas, and its concentrations in aquatic areas are heavily influenced by anthropogenic activities, especially human-induced eutrophication, polluted river discharge and wastewater treatment plant (WWTP) effluents. Although coastal areas and estuaries contribute large amounts of global oceanic CH4 emissions, the relative contributions of different sources have not been well determined. The Tamsui River located in northern Taiwan is an urban river flowing through populated cities and thus likely carries large amounts of contaminants, such as nutrients and organic matter to the estuary. In this study, we characterized the spatial distribution and seasonal variations in CH4 in the Tamsui River estuary adjacent marine areas. The sea-to-air CH4 fluxes were also estimated to quantify the strength of the study area as an atmospheric CH4 source. Our results showed that CH4 concentrations in coastal sea areas were influenced by WWTP effluents, sediment and freshwater inputs. Thus, river discharge and nutrient levels as well as strong vertical mixing and disturbances might increase CH4 concentrations and emissions. The seasonal surface CH4 concentrations and sea-to-air CH4 fluxes were 13.7±18.7 nM and 41.7±68.0 mol m-2 d-1 in autumn; 29.3±19.8 nM and 61.3±44.6 mol m-2 d-1 in spring; 21.8±13.9 nM and 37.0±26.2 mol m-2 d-1 in summer; and 27.0±21.4 nM and 85.9±75.4 mol m-2 d-1 in winter.